Assessment of Radiological Parameters of Lordosis in Chronic Low Back Pain: A Case-control Study - Sudhir Singh; Sankalp Singh; Vijay Pratap Singh (Journal of Clinical and Diagnostic Research)
Introduction: Low Back Pain (LBP) is a global health problem with a multifactorial aetiology. Many clinicians believe that changes in lumbar lordosis contribute to LBP. The normal range of lordosis has not yet been agreed upon; hence, the practice of assessing the parameters of lordosis on sagittal radiographs becomes irrelevant, adding to treatment costs and exposing patients to radiation risk. Consequently, the practice of measuring lordosis needs to be re-evaluated. Aim: To determine the Lumbar Lordotic Angle (LLA) and Lumbosacral Angle (LSA) in individuals with and without LBP. Materials and Methods: This case-control study was conducted from November 2022 to March 2024 at Teerthankar Mahaveer Medical College, a tertiary care hospital, Moradabad, Uttar Pradesh, India. One hundred patients aged between 18 and 50 years with chronic non specific LBP were recruited as cases, matched for age, gender and Body Mass Index (BMI). Similarly, 100 healthy volunteers were taken as controls, also matched for these parameters. LSA and LLA were recorded on sagittal radiographs of all subjects, and the data were analysed statistically. Results: The cases and controls were similar with respect to age (p-value=0.407), gender (p-value=0.315), and mean BMI (p-value=0.239). The mean LSA was 34.17±5.86° (M: 35.19±6.86°; F: 33.55±5.07°) in the case group and 36.69±6.72° (M: 37.68±6.78°; F: 35.87±6.63°) in the control group (p-value=0.001). The mean LLA was 50.04±9.09° (M: 53.99±8.93°; F: 48.25±8.55°) in cases and 49.60±9.77° (M: 48.78±9.69°; F: 50.30±9.88°) in controls (p-value=0.737). LBP cases showed decreased LSA in individuals aged 31-40 years (p-value=0.013), in females (p-value=0.02), and in overweight individuals (p-value=0.002), alongside increased LLA in males (p-value=0.001); however, the difference in angles was only observed in the 20-40 years age range. LLA and LSA did not show any significant association or correlation with age, gender, BMI and VAS. Conclusion: The results indicate that LLA does not vary between those with and without LBP. The LSA was significantly lower in patients with LBP. Both LSA and LLA do not demonstrate a clear association and show an insignificant weak correlation with age, gender, BMI and VAS in both cases and controls.